Membandingkan Konsep Pajak (Kharâj) Yahya bin Adam (758-818 H) dan Imam al-Mawardi (974-1058 H) - Rahmad Hakim (TSAQAFAH, 2016)
The rise of Islamic civilization since the 6 th century up to the 18 th century is a historical fact that can not be negated. Starting from the establishment of the State of Medina by the Prophet Muhammad until the Ottoman Dinasty. The course of history that sustained over centuries, has a significant influence on the development of Islamic civilization, at least in terms of taxation which commonly called as kharâj. In the hands of Islam, was created a various principles of the state, especially on the financial and monetary aspect. The creation of financial system for the state is one of proof for the creation of the state’s basic principles in order to achieve justice and prosperity of mankind. This paper aims to discuss in-depth analysis related to the concept of taxation in Islam through literature method. In order to obtain deeper analysis, the author chose two characters who was concerns in the field of taxation in the history of Islamic Economic thought, namely Yahya bin Adam in his al-Kharâj and Imam al-Mawardi in his al-Ahkâm al-Sultâniyah. The conclusion from this study is that there are some similarities between the two ideas. On the other hand, according to the author, Imam al-Mawardi’s theory of taxation has two advantages; first, his futuristic theory of taxation and second, his contextual theory of taxation that possible to be applied in the present time. Given the complexity of the problems that occurred during his life.